Efeito da superexpressão do gene OVP1 em parâmetros fisiológicos e caracteres relacionados a produtividade de grãos em arroz de terras altas - Rocha, Dhiôvanna Corrêia (2021)
Population growth, climate change and reduction of area for cultivation are some of challenges that agriculture has been facing in recent years, making it necessary to develop cultivars to meet global demand for food. The highland rice cultivar BRSMG Curinga was transformed via Agrobacterium tumefaciens to overexpress the OVP1 gene. OVP1 gene encodes a protein that pumps protons across membranes using the energy from breaking down inorganic pyrophosphate (Pi) and trigger various metabolic and morphological changes in plants. This work aimed to evaluate the performance of some traits related to grain yield, physiology, and gene expression of genetically modified (GM) rice that overexpressed the OVP1 gene (OVP1-E4) compared to the non-genetically modified (NGM). Two experiments were carried out under controlled conditions at Embrapa Rice and Beans in the 2018/2019 and 2019/2020 seasons. The experimental design was based on complete randomized blocks with eight repetitions for the first experiment and four for the second. Some traits related to grain yield in rice and physiological data were collected with the IRGA device during the reproductive phase (stages R2, R3, R4, R6, R7, R8 e R9), making it possible to estimate the carboxylation efficiency (A/Ci) and the instantaneous (A/E) and intrinsic water (A/Gs) use efficiency were estimated. The OVP1 gene was quantified by RT-qPCR and the transcriptome was evaluated through RNAseq. A joint analysis of variance (p<0.05) was performed for the collected data in the two experiments. The OVP1-E4 event stood out for producing 21% more grains per panicle and 31% more filled grains than NGM. Significant physiological changes were found during grain filling (R6). At this stage, the OVP1-E4 event showed an increase of 61% in the photosynthetic rate and was 89% more efficient in carboxylation than NGM, without the occurrence of an increase in stomatal conductance and in the transpiratory rate. GM plants were also more efficient in using water. OVP1 gene was more expressed in the OVP1-E4 event during the grain filling period, and genes involved in photosynthesis were up-regulated in GM plants. Overexpression of OVP1 gene resulted in plants with physiological and phenotypic changes that pave the way for the development of rice cultivars more physiologically more efficient and more productive.